The Romantic Veil (of Perception): American Transcendentalism and British Romanticism as a Continuation of Lockean Empiricism - Knirsch, Christian (Current Objectives of Postgraduate American Studies, 2012)
When it comes to the epistemological basis of British romanticism and American transcendentalism, a traditional approach would certainly refer to Kant’s transcendental philosophy which is commonly considered an antithesis to Locke’s empiricism. A new trend in philosophical research now suggests that romantic theories are an addition to rather than a refutation of empiricism. This essay traces the interdependencies between transcendental thought and empiricism in the writings of Coleridge and Emerson.